ANALISIS KUALITAS PRODUK, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN THAI TEA PADA GENERASI MILLENIAL - Almira Febrida, (2020)
Based on data from the 2015-2020 Top Brand Index For Teens Food and Beverage Category Bubble Drink, Hop-hop sales increased dramatically in 2016 after previously exceeding Chatime. Which in 2015 the level of Hop-hop sales was above Chatime with a difference of 19.4%, but then in 2016 until now Chatime switched to surpass Hop-hop as the most favorite beverage brand with a percentage difference of 14.1% . This indicated that Hop-hop's customer satisfaction was difficult. Related to the purpose of this research is to study, analyze, and prove related to product quality, service quality, and brand image to customer satisfaction. The method in this study is quantitative with the participation of consumers who have bought Thai Tea in Hop-hop which is a millennial generation. Samples taken as many as 75 respondents with a puposive sampling method. And distributing questionnaires to consumers of Thai Hophop. Tea during the data collection process. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is SmartPLS 3.0 (Partial Least Square). The results showed that the large value of the path coefficient for product quality amounted to 0.396, service quality amounted to 0.343, and brand image of 0.177 had a significant effect and R-Square of 0.588 on consumer satisfaction of Thai Tea Hop-hop.